2019
DOI: 10.1155/2019/5183261
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Extraction Conditions on Chemical and Thermal Characteristics of Kappa-Carrageenan Extracted fromHypnea bryoides

Abstract: Hypnea bryoides collected from the Arabian Sea on the southern coast of Oman was investigated for κ-carrageenan optimal extraction conditions. The effects of different conditions of alkali treatment (4, 6, and 8% w/v NaOH), temperatures (70, 75, and 80°C), and time (2, 2.75, 3.5 hours) on carrageenan yield and chemical and thermal properties were evaluated. Yield was significantly affected by alkaline concentration and temperature, with highest value of 26.74 ± 5.01%. Molecular weights of the extracted carrage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 42 publications
1
13
0
2
Order By: Relevance
“…In G. turuturu, pH adjustment did not significantly impact the water-based extraction at room temperature, because whatever was being extracted had low molecular weight carbohydrates for which protonation was less relevant in terms of solubility than higher-molecular weight ones. At a near-boiling temperature, however, a linear increase of yield with pH suggested that alkalinity promoted extraction, which was expected since alkaline hydrolysis was one of the methods to dissolve cellulosic biomass and solvate their carbohydrates [44]. With ethanol in the solvent, this trend was reversed and we observed an almost-linear increase of yield and decreased pH.…”
Section: Discussionmentioning
confidence: 52%
“…In G. turuturu, pH adjustment did not significantly impact the water-based extraction at room temperature, because whatever was being extracted had low molecular weight carbohydrates for which protonation was less relevant in terms of solubility than higher-molecular weight ones. At a near-boiling temperature, however, a linear increase of yield with pH suggested that alkalinity promoted extraction, which was expected since alkaline hydrolysis was one of the methods to dissolve cellulosic biomass and solvate their carbohydrates [44]. With ethanol in the solvent, this trend was reversed and we observed an almost-linear increase of yield and decreased pH.…”
Section: Discussionmentioning
confidence: 52%
“…Fur showed the greatest shift in transition temperatures and in thermal hysteresis, probably due to the greater degradation of polysaccharide. A positive correlation between molecular weight and melting and gelling temperatures has been previously reported [ 15 , 40 ].…”
Section: Resultsmentioning
confidence: 54%
“…Kappa-Carrageenan has a 3,6-AG bridge and one sulfate ester group. Because of this, it is less hydrophilic and less soluble in water [85]. Figure 6I,J show the interaction between Kappa-Carrageenan and the target M pro protein of SARS-CoV-2.…”
Section: Dolabellinmentioning
confidence: 99%